Digital preservation for libraries, archives, [and] museums - Corrado, Edward M., 1971-; Moulaison, Heather Lea (Rowman & Littlefield, 2014)
Development, objectives, and principles -- Underlying models and organization -- Major differences between RDA and AACR2 -- Attributes of manifestations and items -- Attributes of works and expressions -- Attributes of persons, families, corporate bodies, and places -- Recording relationships -- Creating and interpreting bibliographic records for books -- Creating and interpreting bibliographic records for nonbook resources -- Creating and interpreting authority records